O GRUPO DE ESTUDOS E PESQUISAS EM GEOMETRIA (GEPGEO) COMO UM ESPAÇO DE APRENDER DOCENTE: CONTRIBUIÇÕES NO DESENVOLVIMENTO DO CONHECIMENTO MATEMÁTICO PARA O ENSINO - Soares, Gabriel de Oliveira (2023)
This study is part of the research line Teacher Education, of the Postgraduate Program in Science and Mathematics Teaching at the Franciscan University, and has as its generating theme the contributions of collaborative study groups to teacher education. In this article, we tried to delineate contributions to the development of the domains of Mathematical Knowledge for Teaching and in teacher education from the participation in the Group for Study and Research in Geometry (GEPGEO), linked to this graduate program. The theoretical framework used to support this study is the Mathematical Knowledge Base for Teaching, authored by Ball, Thames and Phelps (2008), and has as indicators the questions proposed by Hurrel (2008). This is a qualitative research, of the case study type, in which 13 members of the study group participated. Data were collected through 31 periodic meetings of the group, held from September 2019 to December 2020, which were videotaped and analyzed according to the methodology proposed by Powell, Francisco, and Maher (2004). In addition, an autobiographical narrative was developed in order to establish personal contributions from participation in the group. From the analyses, it was possible to verify that the participation in GEPGEO promoted the mobilization of the six domains of Mathematical Knowledge for Teaching proposed by the authors, besides listing contributions in the deepening of theoretical and practical knowledge about Mathematics and the teaching of this curricular component for its participants. Finally, we reaffirm the formative potential that collaborative spaces for teachers have for the professional development of their participants.